Histopathological Study of Colorectal Lesions and Its Correlation with Colonoscopic Findings - Shrestha, Richa; Adhikari, Milan; Bharti, Shiv Vansh; Shrestha, Anil (Journal of Nepalgunj Medical College, 2023)
Introduction: Colorectal lesions are diverse and have variety of symptoms which overlap with benign and malignant conditions. Cancerous conditions are common in this region, thus early diagnosis influences the response to management. Colonoscopy and histopathological study of lesions is crucial in diagnosis and management of neoplastic conditions.Aims: To study the correlation of the colonoscopic and histopathological findings in colorectal lesions and spectrum of colorectal lesions.Methods: This is a hospital based prospective cross-sectional study conducted over the period of 16 months from January 2021 to June 2022 in department of Pathology, Nepalgunj Medical College Teaching Hospital (NGMCTH), Kohalpur, Nepal. Informed verbal consent from the patient was obtained. Patients who have undergone colonoscopy were included in the study whose corresponding histopathological samples were also received in the form of either large or small biopsies.Results: Total 95 cases were included in the study which showed male preponderance overall as well as in malignant conditions. Adenocarcinoma was most common histopathological finding followed by nonspecific chronic colitis. Most common clinical complain was bleeding per rectum and most common colonoscopic finding was ulceroproliferative lesion. The correlation between colonoscopy and histopathology done as benign and malignant was statically significant.Conclusion: The current study revealed a good correlation between colonoscopic and histopathological findings. Morphological study helps in identification of disease for early diagnosis and management, especially in malignancy.